The Multiscale TROPIcal CatchmentS critical zone observatory M‐TROPICS dataset III: Hydro‐geochemical monitoring of the Mule Hole catchment, south India - Riotte, Jean; Ruiz, Laurent; Audry, Stéphane; Baud, Benjamin; Bedimo Bedimo, Jean‐Pierre; Boithias, Laurie; Braun, Jean‐Jacques; Dupré, Bernard; Duprey, Jean‐Louis; Faucheux, Mikael; Lagane, Christelle; Marechal, Jean‐Christophe; et al. (Hydrological processes, 2021)
Despite the importance of tropical ecosystems for climate regulation, biodiversity, water and nutrient cycles, only a few Critical Zone Observatories (CZOs) are located in the tropics. Among these, most are in humid climates, while very few data exist for semi‐arid and sub‐humid climates, due to the difficulty of estimating hydro‐geochemical balances in catchments with ephemeral streams. We contribute to fill this gap by presenting a meteorological and hydro‐geochemical dataset acquired at the Mule Hole catchment (4.1 km2), a pristine dry deciduous forest located in a biosphere reserve in south India. The dataset consists of time series of variables related to (i) meteorology, including rainfall, air temperature, relative humidity, wind speed and direction, and global radiation, (ii) hydrology, including water level and discharge at the catchment outlet, (iii) hydrogeology, including manual (monthly) and/or automated (from 15 min to hourly) groundwater levels in nine piezometers and (iv) geochemistry, including suspended sediment content in the stream and chemical composition of rainfall (event based), groundwater (monthly sampling) and stream water (storm events, 15 min to hourly frequency with an automatic sampler). The time series extend from 2003 to 2019. Measurement errors are minimized by frequent calibration of sensors and quality checks, both in the field and in the laboratory. Despite these precautions, several data gaps exist, due to occasional access restriction to the site and instrument destruction by wildlife. Results show that large seasonal and interannual variations of climatic conditions were reflected in the large variations of stream flow and groundwater recharge, as well as in water chemical composition. Notably, they reveal a long‐term evolution of groundwater storage, suggesting hydrogeological cycles on a decadal scale. This dataset, alone or in combination with other data, has already allowed to better understand water and element cycling in tropical dry forests, and the role of forest diversity on biogeochemical cycles. As tropical ecosystems are underrepresented by Critical Zone Observatories, we expect this data note to be valuable for the global scientific community. This datanote presents the meteorological and hydro‐geochemical dataset of a sub‐humid tropical catchment in south India, Mule Hole, which is covered by a pristine dry deciduous forest. The monitoring, initiated in 2003, allowed to calculate annual water and biogeochemical budgets. It contributed to reveal the role of monsoon decadal fluctuations and vegetation on the critical zone functioning in this ecosystem.